Integrating moral-spiritual values into digital English materials: Effects on learning enjoyment, engagement, and ethical language use - Muhammad Roda'i; Mehmet Cuma Tahiroglu; Harmita Sari; Ming Chou Liu (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2026)
This study aims to analyze the effect of Moral Spiritual Integrated Digital Materials and Perceived Ease of Use on Ethical Language Use Behavior in digital-based language learning, considering the role of Learning Enjoyment and Student Interest as mediating variables. Using a quantitative survey method, data were collected from 150 students through questionnaires. The respondents were selected using purposive sampling, with the criterion that they had used digital learning media in the learning process. Data analysis was performed using Structural Equation Modelling with Partial Least Squares (SEM-PLS), aided by the SmartPLS application. The results showed that Moral Spiritual Integrated Digital Materials and Perceived Ease of Use had a significant positive effect on Learning Enjoyment. Additionallu, Perceived Ease of Use also has a significant positive effect on Ethical Language Use Behavior. Furthermore, Learning Enjoyment is proven to have a significant positive effect on Student Interest. However, the direct effect of Moral Spiritual Integrated Digital Materials on Ethical Language Use Behavior is not significant. The analysis results also show that Learning Enjoyment and Student Interest act as mediating variables in the relationship between independent variables and Ethical Language Use Behavior.